Evaluasi jumlah saluran akar gigi premolar pertama atas menggunakan teknik radiografi periapikal pararel dan Cone Beam Computed Tomography - Sandy Pamadya; Mirza Aryanto; Nurani Hayati; Johannes Dhartono (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2021)
Objectives: Maxillary and mandibular first premolars are amongst the teeth that has a risk to caries and needed to be treated. These teeth were varied in term of root and root canal amount. A successful root canal treatment in premolar teeth is highly dependent on the identification of the number and shape of root canals according to Vertucci. Radiographs are still the main choice in helping dentists establish an adequate diagnosis and treatment plan for root canal treatment. Conventional radiographs produce two-dimensional images which often cause difficulties in interpreting the resulting radiograph images. Modern imaging modalities such as CBCT can be used to produce a more accurate image. The aim of this study was to determine whether there is a difference in the number of root canals of maxillary first premolar teeth displayed on periapical radiographs and CBCT and also to test the accuracy of periapical radiographs in detecting the number of root canals of maxillary first premolar teeth compared to CBCT radiographs. Materials and Methods: This research was experimented by performing periapical radiological examinations and CBCT on 50 maxillary premolar teeth samples, then evaluating the number of visible root canals. Results: The results showed that there was a significant difference in the number of root canals seen on the periapical radiograph and CBCT. Conclusion: CBCT radiographs have the advantage of detecting the number of root canals of maxillary premolars more accurately than periapical radiographs.